Identification of Intelligent Participants Using Profile Matching Method (Case Study at Senior High School 1 Sungai Aur) - Putra, Nursaka; Nas, Chairun; Alwendi; Samosir, Khairunnisa; Aldo, Dasril (Journal of physics. Conference series, 2021)
Determining the right candidate as an envoy to take part in a quiz contest can increase the chances of becoming a champion. To achieve these opportunities the school must be more selective in choosing the students who excel in the subjects to be contested. In the selection of students, intelligent representatives are usually the school only takes students who get the first rank of each class, even though it is not necessarily that the students master the lessons to be contested. Can help Senior High School 1 Sungai Aur in making quick and accurate decisions for the selection of representatives of quiz competition. Data obtained from the Senior High School 1 Sungai Aur in the form of student data with a sample of 20 students who have the potential in their respective subjects. Furthermore, the data will be analyzed using the Profile Matching method. The results of this study, it was decided that only 12 participants from 20 samples were passed. Processing results found that there were 3 participants whose decisions were different from those of the school and 9 participants with the same decision. So that the value of data processing accuracy is 75% and an error value of 25% of the 12 participants determined. It can be concluded that this study can help the school to determine students who have the right to represent their school in a quiz competition.